Individual and contextual covariates of burnout: a cross-sectional nationwide study of French teachers - Nerrière Eléna; Gilbert Fabien; Brosselin Pauline; Vercambre Marie-Noël; Kovess-Masféty Viviane (BMC, 2009)
Abstract Background Limited information on the covariates of burnout syndrome in French teachers is available. The aim of this study was to evaluate the relative contributions of individual and contextual factors on the three burnout dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. Methods The source data come from an epidemiological postal survey on physical and mental health conducted in 2005 among 20,099 education workers (in activity or retired) selected at random from the health plan records of the national education system. The response rate was 52.4%. Teachers in activity currently giving classes to students who participated in the survey (n = 3,940) were invited to complete a self-administered questionnaire including the Maslach Burnout Inventory. 2,558 teachers provided complete data (64.9%). Variables associated with high emotional exhaustion (highest quartile of score), high depersonalization (highest quartile), and reduced personal accomplishment (lowest quartile) were evaluated using multivariate logistic regression. Studied variables referred to demographic characteristics, socio-professional environment, job dissatisfaction, experienced difficulties at work, and teaching motivations. Results Different variables were associated with each burnout dimension. Female teachers were more susceptible to high emotional exhaustion and reduced personal accomplishment, whereas male teachers were more susceptible to high depersonalization. Elementary school teachers were more susceptible to high emotional exhaustion, but less susceptible to high depersonalization and reduced personal accomplishment than their higher school level counterparts. Experienced difficulties with pupils were associated with all three dimensions. A socio-economically underprivileged school neighbourhood was also related to high emotional exhaustion and high depersonalization. Conclusion Programs to enhance teaching environment might be an interesting approach to try to prevent burnout. It would be useful to take the different dimensions into account in planning the intervention.